Efektivitas Model Problem Based Learning Berbasis Realistic Mathematic Education Untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis Siswa Kelas VIII - Nur Afifah; Fadhilah Rahmawati; Yesi Franita (Peneliti.net, 2023)
This study aims to see the difference in the average ability to understand students' mathematical concepts using the Problem Based Learning (PBL) model based on Realistic Mathematics Education (RME) with a direct learning model and to see how effective the Problem Based Learning (PBL) model based on Realistic Mathematics Education (RME) is to improve students' ability to understand mathematical concepts on flat side room building material. This research approach is quantitatively through pretest-posttest nonequivalent control group design. The population of this study was all grade VIII students of SMP Negeri 1 Tegalrejo, while until they were selected through cluster random sampling where classes VIII A and VIII C were selected as samples. Research data was collected through tests of the ability to understand mathematical concepts in the form of pretest and posttest. Furthermore, the data was analyzed through SPSS with paired sample t-test and N-Gain test. The results showed that 1) there was an average difference between the RME-based PBL model and the direct learning model; and 2) RME-based PBL models are more effective for improving students' ability to understand mathematical concepts.